2006
DOI: 10.17161/kwpl.1808.1229
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Assimilation in Urban Jordanian Arabic

Abstract: This study reports patterns of phonological assimilation in consonant clusters in Urban Jordanian Arabic (UJA). We examine all possible C 1 C 2 combinations across a word boundary as well as the concatenations of consonant-final prefixes //in/ and //il/ and consonant-initial stems. The data show that place assimilation in UJA is regressive, and it can occur both across major articulators and within the same articulator (for coronals). UJA also exhibits voicing assimilation and emphasis assimilation. The main t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Finally, /rˤ/ in RPA partakes in coronal sonorant assimilation, by which /l/ fully assimilates to /rˤ/ and /n/ to /rˤ, l/; see (9). The process is also reported in Syrian (Cowell 1964), Urban Jordanian (Zuraiq & Zhang 2006), Northern Rural Jordanian (Bani-Yasin & Owens 1987), and Southern Rural Jordanian (Al Huneety 2015), among other dialects in this group. A related observation by McCarthy (1986), cited in Herzallah (1990), is that the consonants /n, l, rˤ/ do not co-occur in the same root.…”
Section: (18)mentioning
confidence: 58%
“…Finally, /rˤ/ in RPA partakes in coronal sonorant assimilation, by which /l/ fully assimilates to /rˤ/ and /n/ to /rˤ, l/; see (9). The process is also reported in Syrian (Cowell 1964), Urban Jordanian (Zuraiq & Zhang 2006), Northern Rural Jordanian (Bani-Yasin & Owens 1987), and Southern Rural Jordanian (Al Huneety 2015), among other dialects in this group. A related observation by McCarthy (1986), cited in Herzallah (1990), is that the consonants /n, l, rˤ/ do not co-occur in the same root.…”
Section: (18)mentioning
confidence: 58%
“…Thus, the emphatic syllable is the preferred surface structure in this Jordanian subvariety under study, which is different from the preferred structure of ES found in other varieties, such as emphasis (conditionally) spreading into the whole word in Palestinian Arabic (Davis 1995), San'ani Arabic (Watson 1999), Cairene Arabic (Youssef 2013), Djelfa Algerian Arabic (Slimani 2018), and Libyan Arabic (Algryani 2014). Concerning other Jordanian subvarieties-Kufr El-ma' (Bani-Yasin & Owens 1987), Wadi Ramm (Al-Mashaqba 2015) and Juffin (Huneety & Mashaqba 2016)--the authors argue, with some variation, that there are opaque sounds blocking rightward spread (such as /i/ and /y/). Leftward spread, on the other hand, is absolute.…”
Section: Discussionmentioning
confidence: 99%
“…In Jordan, Modern Standard Arabic (MSA) is considered the official language and is commonly used in formal situations such as public speeches, news announcements, and religious services. Besides, there are four regional dialects which are spoken locally in day-to-day communications: Urban, Rural, Bedouin, and Ghorani (Zuraiq and Zhang 2006). The rural dialect is further divided into two subdialects: rural Palestinian and rural Jordanian.…”
Section: The Dialectal Settingmentioning
confidence: 99%